Circulating natural killer (NK) and gama / delta T cells decrease soon after infection of rhesus macaques with lymphocytic choriomeningitis virus (2009)
ABSTRACT: Rhesus macaques infected with the WE strain of lymphocytic choriomeningitis virus (LCMV-WE) serve as a model for human infection with Lassa fever virus. To identify the earliest events of acute infection, rhesus macaques were monitored immediately after lethal infection for changes in peripheral blood mononuclear cells (PBMCs). Changes in CD3, CD4, CD8 and CD20 subsets did not vary outside the normal fluctuations of these blood cell populations; however, natural killer (NK) and γδ T cells increased slightly on day 1 and then decreased significantly after two days. The NK subsets responsible for the decrease were primarily CD3-CD8+ or CD3-CD16+ and not the NKT (primarily CD3+CD56+) subset. Macaques infected with a non-virulent arenavirus, LCMV-Armstrong, showed a similar drop in circulating NK and γδ T cells, indicating that this is not a pathogenic event. Vγ9 T cells, representing the majority of circulating γδ T cells in rhesus macaques, displayed significant apoptosis when incubated with LCMV in cell culture; however, the low amount of cell death for virus-co-cultured NK cells was insufficient to account for the observed disappearance of this subset. Our observations in primates are similar to those seen in LCMV-infected mice, where decreased circulating NK cells were attributed to margination and cell death. Thus, the disappearance of these cells during acute hemorrhagic fever in rhesus macaques may be a cytokine-induced lymphopenia common to many virus infections.